Clinical features, functional status, and quality of life in patients with late-onset familial Mediterranean fever - GEZER, HALİSE HANDE; ÖZ, NURAN; DURUÖZ, MEHMET TUNCAY (My University, 2023)
OBJECTIVE: This study aimed to determine the frequency of late-onset familial Mediterranean fever (FMF) and compare the clinical and genetic features, functional status, and health-related quality of life (QoL) of patients with early-onset and late-onset disease. METHODS: Patients with onset of symptoms ≤20 and >20 years of age were classified as early-onset and late-onset FMF, respectively. The clinical characteristics, MEFV gene mutations, and Pras disease severity scores were recorded. Physical disability and QoL were assessed with the health assessment questionnaire (HAQ) and short form 36 (SF-36), respectively. RESULTS: The mean age of 138 patients (104 women and 34 men) was 37.7±12.69 years. The percentages of patients with early-and late-onset FMF were 68.1% and 31.9%, respectively. Female sex, mild disease, arthritis, and sacroiliitis were more common in the late-onset group (p0.05). CONCLUSION: The patients with late-onset FMF had a female predominance, a shorter delay of diagnosis, more frequent arthritis and sacroiliitis, a less frequent homozygous M694V mutation, and a milder disease severity than those with early-on-set disease. Physical function and health-related QoL were similar in early-and late-onset FMF groups.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Disease activity; familial Mediterranean fever; functional status; quality of life